Sustainability Assessment of a Residential Building using a Life Cycle Assessment Approach - Janjua, S.; Sarker, Prabir; Biswas, Wahidul (The Italian Association of Chemical Engineering, 2019)
Building and construction industry is responsible for resource scarcity, global warming impacts, land use changes and the loss of bio-diversity, which have direct and indirect socio-economic implications. Sustainable building design is thus inevitable through the selection of highly durable and less energy intensive-materials that could reduce environmental degradation in an economically viable and socially acceptable manner. This paper presents the life cycle sustainability assessment (LCSA) framework to assess the environmental, social and economic objectives of residential buildings. Two buildings of different material compositions have been used to test this framework. Firstly, the service life of this building has been calculated as durability of building materials play a key role in enhancing resource conservation for the future generations. A factor method has been used to carry out the service life of each component of the building envelope. The minimum estimated service life of building systems is considered as the overall service life of building components. Secondly, a life cycle assessment framework utilising environmental life cycle assessment, life cycle costing and social life cycle assessment have been utilised to determine environmental, economic and social indicators of the studied buildings. All these triple bottom line indicators in this framework have been calculated on an annual basis in order to capture the advantage of increased service life of buildings. This framework will be applied to assess the sustainability performance of alternative buildings for comparative analysis and to find out the most sustainable building option.